The global city: on the streets of Renaissance Lisbon - Jordan Gschwend, Annemarie; Lowe, K. J. P. (Paul Holberton publishing, 2015)
The volume highlights the unique status of Lisbon as an entrepôt for curiosities, luxury goods and wild animals. As the Portuguese trading empire of the fifteenth and sixteenth century expanded sea-routes and networks from West Africa to India and the Far East, non-European cargoes were brought back to Renaissance Lisbon. Many rarities were earmarked for the Portuguese court, but simultaneously exclusive items were readily available for sale on the Rua Nova, the Lisbon equivalent of Bond Street or Fifth Avenue. Specialized shops offered West African and Ceylonese ivories, raffia and Asian textiles, rock crystals, Ming porcelain, Chinese and Ryukyuan lacquerware, jewellery, precious stones, naturalia and exotic animal byproducts. Lisbon was also a hub of distribution for overseas goods to other courts and cities in Europe. The cross-cultural and artistic influences between Lisbon and Portuguese Africa and Asia at this date will be re-assessed --